Pengaruh Budaya Sekolah Terhadap Keterampilan Abad 21 Peserta Didik SMA Negeri 36 Jakarta Dimediasi oleh Motivasi Berprestasi - Stevani Sherly Anggreni; Siti Nurjanah; Fitra Dilla Lestari (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the influence of school culture on 21st-century skills of students of SMA Negeri 36 Jakarta mediated by achievement motivation. This study uses a quantitative method research design with the type of research used is explanatory, the population in this study were all students of SMA Negeri 36 Jakarta. The analysis technique used in testing this research is the Partial Least Square (PLS) method. The conclusions that can be drawn are: School culture positively and significantly improves the 21st-century skills of class XII students of SMA Negeri 36 Jakarta. The stronger and more positive the school culture applied, the higher the level of mastery of 21st-century skills (critical thinking, creativity, collaboration, and communication) possessed by students. Achievement motivation positively and significantly improves the 21st-century skills of class XII students of SMA Negeri 36 Jakarta. The higher the motivation of students to achieve, the students will continue to hone their skills so that mastery of 21st-century skills (critical thinking, creativity, collaboration, and communication) becomes stronger. School culture positively and significantly stimulates the motivation to achieve among 12th-grade students at SMA Negeri 36 Jakarta. The implementation of a positive school culture encourages students to increase their desire to achieve. School culture positively and significantly enhances 21st-century skills in 12th-grade students at SMA Negeri 36 Jakarta through achievement motivation. A positive school culture provides positive encouragement for students to achieve. With increased achievement motivation, students' mastery of 21st-century skills also increases. This indicates an indirect effect.